Topological phase diagram of coupled spinless p-wave superconductors. (May 2019) - Maiellaro, A; Romeo, F; Citro, R
Abstract: We investigate the topological properties of a ladder given by two one dimensional p-wave superconductors coupled together site to site by transversal hopping t . For small t, we also derive an effective model whose simpler form is feasible to implement some braiding procedures proposed in the literature.